World sheet instantons via the Myers effect and N = 1* quiver superpotentials - Timothy Hollowood (Journal of High Energy Physics, 2002)
In this note we explore the stringy interpretation of non-perturbative ef- fects in N = 1∗ deformations of the Ak−1 quiver models. For certain types of deforma- tions we argue that the massive vacua are described by Nk fractional D3-branes at the orbifold polarizing into k concentric 5-brane spheres each carrying fractional brane charge. The polarization of the D3-branes induces a polarization of D-instantons into string world-sheets wrapped on the Myers spheres. We show that the superpotentials in these models are indeed generated by these world-sheet instantons. We point out that for certain parameter values the condensates yield the exact superpotential for a relevant deformation of the Klebanov-Witten conifold theory.